Look again - Scottoline, Lisa. (New York : St. Martin's Griffen, 2009)
When reporter Ellen Gleeson gets a "Have You Seen This Child?" flyer in the mail, her heart stops--the child in the photo is identical to her adopted son, Will.
Keywords: Women journalists -- Fiction; Missing children -- Fiction; Adopted children -- Fiction; Suspense fiction